Crystal structure of 3-ethyl-1-[(E)-[(2E)-3-phenylprop-2-en-1-ylidene]amino]thiourea, C12H15N3S - Tan, Ming Yueh; Ho, Sheng Zhou; Tan, Kong Wai; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C12H15N3S, orthorhombic, Pbca (no. 61), a = 11.9612(5) Å, b = 8.1215(3) Å, c = 27.5865(12) Å, V = 2679.83(19) Å3, Z = 8, Rgt(F) = 0.0520, wRref(F2) = 0.1514, T = 293(2) K.